PEMBANGUNAN HUKUM KEDAULATAN PERAIRAN DALAM MEWUJUDKAN VISI INDONESIA SEBAGAI POROS MARITIM DUNIA - Ainun Najib (HUKMY : Jurnal Hukum, 2025)
Indonesia's vision to become the world's maritime axis cannot be separated from developing maritime zones and upholding maritime sovereignty. To achieve this vision, Indonesia must prioritize the sustainable development of marine resources and strengthen maritime jurisdiction and surveillance capabilities. This requires integrated collaboration and coordination between various stakeholders, including the government, the private sector, and local communities. Realizing Indonesia's vision as the world's maritime axis requires a comprehensive and integrated approach to developing marine zones and upholding maritime sovereignty. Through the historical spirit of past glories in the maritime sector, Indonesia can become a leading maritime country and contribute to global efforts to encourage conservation and utilization of the sea by prioritizing sustainable development and strengthening its maritime capabilities by the direction of national development and the provisions of international maritime law. This research is normative legal research with a statutory and historical approach. Data analysis uses descriptive and constructive analysis to reveal legal construction and compile arguments based on premises that form the basis of the concept for the direction of marine zone development and upholding maritime sovereignty in realizing Indonesia's vision as the world's maritime axis.